hMG addition affects the change in progesterone level during IVF stimulation and LBR: a retrospective cohort study - Victoria G. Wesevich; Serin I. Seckin; Dawn A. Kelk; Amanda N. Kallen; Pinar H. Kodaman (BMC, 2023)
Abstract Background Premature progesterone (P) rise during IVF stimulation reduces endometrial receptivity and is associated with lower pregnancy rates following embryo transfer (ET), which can influence provider recommendation for fresh or frozen ET. This study aimed to determine whether change in P level between in IVF baseline and trigger (𝚫P) is predictive of pregnancy outcome following fresh ET, and whether the ratio of gonadotropins influences P rise and, as a result, clinical pregnancy outcomes: clinical pregnancy rate (CPR) and live birth rates (LBR). Methods Retrospective cohort study at a single fertility center at an academic institution. The peak P level and 𝚫P were modeled in relation to prediction of CPR and LBR, and the ratios of hMG:rFSH were also modeled in relation to prediction of peak P level on day of trigger, 𝚫P, and CPR/LBR in a total of 291 patients undergoing fresh embryo transfer after controlled ovarian hyperstimulation-IVF (COH-IVF). Results 𝚫P correlates with CPR, with the most predictive range for success as 𝚫P 0.7-0.85 ng/mL (p = 0.005, 95% CI 0.635, 3.636; predicting CPR of 88.9%). The optimal range for peak P in regard to pregnancy outcome was 0.15-1.349 ng/mL (p = 0.01; 95% CI for coefficient in model 0.48-3.570). A multivariable logistic model for prediction of CPR and LBR using either peak or 𝚫P supported a stronger association between 𝚫P and CPR/LBR as compared to peak P. Furthermore, an hMG:rFSH ratio of > 0.6 was predictive of lowest peak P (p = 0.010, 95% CI 0.035, 0.256) and smallest 𝚫P (p = 0.012, 95% CI 0.030, 0.243) during COH-IVF cycles. Highest CPRs were observed within hMG:rFSH ratios of 0.3-0.4 [75.6% vs. 62.5% within and outside of the range, respectively, (p = 0.023, 95% CI 0.119, 1.618)]. Highest LBRs were seen within the range of 0.3-0.6 hMG:rFSH, [LBR of 55.4% vs. 41.4% (p = 0.010, 95% CI 0.176, 1.311)]. Conclusions Our data supports use of 𝚫P to best predict pregnancy rates and therefore can improve clinical decision making as to when fresh ET is most appropriate. Furthermore, we found optimal gonadotropin ratios can be considered to minimize P rise and to optimize CPR/LBR, emphasizing the importance of luteinizing hormone (LH) activity in COH-IVF cycles.